KONDISI KAPASITAS BANGUNAN SABO KALI GENDOL DENGAN ADANYA KEGIATAN PENAMBANGAN BAHAN GALIAN C PRA ERUPSI 2010 - , Adwiyah Asyifa, ST. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Eruption of Mount Merapi had several annual cycle. The small cycle occur in 2-3 years and large cycle of 10-15 years . At any time there was an eruption will occur the effects of both positive and negative . Sabo dam in controlling sediment disaster and sand mining activities along the path of Kali Gendol become integral to protecting the environment. Mining and rain events greatly affect the capacity of sabo dams and river conditions in Kali Gendol . The research was carried out on sections sabo dams are still actively mining . The volume of incoming sediment sabo dam based on empirical formula of Takahashi (1991 ) and Mizuyama (1977 ) . Sediment balance was analyzed using empirical equation of Shimoda (1995 ) and analyzed on 25 years return period of maximum daily rainfall (R24). Volume of sand mining observed at two points in Kopeng and Glagahmalang. The results of this study shows that the sabo dam in Gendol still effectively works to control sediment flow that will happen in 25 years return period of maximum daily rainfall (R24). Run off sediment just happened to Dam Kaliadem and GE - D7. Sand mining that occurred in the study sites is very active , the average volume of that are 1632.2 m3 for Kopeng site and 1229.3 m3 Glagahmalang site. The main destination for sand minning is Sleman about 64.55 % in Kopeng site and 26.3% in Glagahmalang site.